The Crisis of European Social Sciences: The Case of Money - González Guardiola, Joan (Investigaciones Fenomenológicas, 2014)
Our aim in this article is to put into practice, in the field of social sciences, the principles that Husserl displayed in his book from 1936, "The crisis of European sciences and transcendental phenomenology”. In that seminal work, Husserl reflected on the mathematization of nature and produced an historical meditation on the essence of geometry. Here we will try to extend the reach of Husserlian postulates in order to deal with economics and, more specifically, with the theory of money. We think that, in certain social sciences, and in particular in those with a clear mathematical penchant like economics, the use of formalization often helps to cover an uncritical use of phenomenologically ungrounded idealizations. This fact ultimately results in a massive concealment of the true sense of some of its principal phenomenanamely, money. It is worth mentioning that this concern does not have its roots only in phenomenology, for even academic monetary theory openly acknowledges that we lack an understanding of the meaning of money which could help us clarify and prevent financial crisis and economic collapses. Crisis, in short, are not the result of a deep understanding of the concept of money; on the contrary, they highlight the fact that we don’t really know what money is. Thus, our goal here is to illustrate the possibilities offered by the phenomenological method in its application to the question of money. It is in this sense that the research taking place here can be understood as a “phenomenological critique of monetary theory”. En el presente artículo se pretende llevar a cabo una aplicación de los principios que Husserl lleva a cabo en su obra de 1936, “La crisis de las ciencias europeas y la fenomenología transcendental”, a las ciencias sociales; concretamente, al concepto de dinero. En su obra de 1936, Husserl puso el énfasis en la matematización de la naturaleza, centrándose sobre todo en la meditación histórica sobre la geometría. Pero en el caso de algunas ciencias sociales, como la economía, la utilización libre de construcciones idealizadoras fenomenológicamente infundadas, como en el caso del dinero, está teniendo como resultado un enorme encubrimiento de sentido del fenómeno monetario. Esto no es vivido tan solo desde la feno-menología: desde la propia teoría monetaria se reconoce que estamos faltos de una comprensión del sentido del dinero que nos ayude a clarificar y prevenir de manera suficiente las crisis financieras. Estas crisis no son fruto de que hayamos comprendido demasiado bien el concepto de dinero, sino de que todavía estamos faltos de una comprensión profunda del sentido del dinero. Aquí pretendemos ilustrar las posibilidades que el método fenomenológico ofrece, aplicado al caso del dinero. En este sentido, pueden considerarse las investigaciones que tienen lugar aquí como “crítica fenomenológica de la teoría monetaria”.